1988
DOI: 10.1209/0295-5075/5/4/001
|View full text |Cite
|
Sign up to set email alerts
|

Semi-leptonic Decays of Baryons in the Quark Model

Abstract: Good fits to the experimental values of GA/Gv are obtained when the members of the 1/2+ octet are assumed to be deformed within a constituent quark picture. Close agreement with another independent study favouring the Cabibbo model is obtained. This may help in a better understanding of the relationship between the constituent and the current pictures of the quark.Recent experiments in high-energy hyperon beams have added a new dimension to the study of baryons [l-31. Semi-leptonic decays of the same are of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Later Vento et al [5] found that the ratio of πN ∆ to πN N coupling constant is fitted very well with the same P D ∼ 0.25. The present author has found that the same P D ∼ 0.25 does very well for a large number of physically relevant quantities in the quark model: (a) A comprehensive fit to allowed semileptonic decays of all the 1/2 + baryon octet [6]. (b) Pion-Nucleon-Delta coupling constant, E2/M 1 ratio, double delta coupling constant, constituent quark masses etc.…”
mentioning
confidence: 52%
“…Later Vento et al [5] found that the ratio of πN ∆ to πN N coupling constant is fitted very well with the same P D ∼ 0.25. The present author has found that the same P D ∼ 0.25 does very well for a large number of physically relevant quantities in the quark model: (a) A comprehensive fit to allowed semileptonic decays of all the 1/2 + baryon octet [6]. (b) Pion-Nucleon-Delta coupling constant, E2/M 1 ratio, double delta coupling constant, constituent quark masses etc.…”
mentioning
confidence: 52%
“…The interesting point to note is that Ellis and Jaffe [2] were working within the context of the Cabibbo theory. In our earlier work [7] we had found that our deformed nucleon (in the constituent quark model) was fitting experimental quantities as well as the current quark (Cabibbo model) was doing. Now we find that this parallelism between the 'current' and the 'constituent' descriptions of the quark also persists to the level of Ellis-Jaffe sum rule result.…”
Section: L74mentioning
confidence: 92%
“…However, this is larger than PD=0.2-0.25, which we had been advocating earlier in this letter. In fact, PD = 0.203 had been found to give good fits to several quantities of interest [7] and it is this that we should use. This gives our prediction for g?…”
Section: L74mentioning
confidence: 97%
See 1 more Smart Citation
“…[*(l-r)] l/2 +(yy/4) 1/2 1-fr (4) where x = l -2/3\ y=P' when the correct VBJ wave function (3) is used and x -1 -3/3, y =p when the wave function (2) is used. The advantage of the VBJ wave function is that the same value of y-0.22 fits g A (the axial-vector coupling constant), ju p /jLi n (the ratio of the proton and neutron magnetic moments), the D/F ratio, and r"iv A .…”
mentioning
confidence: 99%